Cetacean diversity on the Parnaiba Delta, Maranhão state, northeastern Brazil - FA. Magalhães; CH. Tosi; RG. Garri; S. Chellappa; FL. Silva (Brazilian Journal of Biology)
The increase in the research of cetacean surveys on the Brazilian coast has brought new data on the distribution of species never reported before. The present work reviews the current knowledge on cetaceans species and extends this knowledge with an analysis of cetaceans stranded in the Parnaiba Delta, on the coast of Maranhão State, Brazil. The studies on cetacean diversity on the coast of the Parnaíba Delta were made from August 2004 to August 2006. Fourteen strandings were reported, representing six distinct species, such as the estuarine dolphin (Sotalia guianensis), humpback whale (Megaptera novaeangliae), Bryde's whales (Balaenoptera edeni), dwarf minke whale (Balaenoptera acutorostrata), pigmy killer whale (Feresa attenuata), sperm whale (Physeter macrocephalus) and two specimens which have not yet been identified. The significant degree of cetacean diversity in the region shows that the Parnaíba Delta is, possibly, of an important area for cetacean studies in Brasil.